How to obtain a more accurate picture of crime through crime statistics: Proposals and methods - Mathias Bug; Kristina Meier (DIW Economic Bulletin, 2014)
This report aims to show the distribution of crime in Germany. For this, police crime statistics (polizeiliche Kriminalstatistik - PKS) are treated so that they integrate dark figures (unreported crime) of crime types along with their specific grade of burden. The different treatments are based on own recent survey data. Two major trends are confirmed by both treatment methods: First, there is a northsouth divide, with the northern regions experiencing a far higher risk of crime. Second, rural/urban differences can be accounted for by the higher levels of everyday crime that affect citizens of towns and cities. These slight differences and changes are more evident and meaningful in state-to-state comparisons rather than looking at Germany as a whole.
Keywords: K14; R19; H56; H77; 330; security; crime; indicator; home affairs; police; federalism; inner security; thread; crime statistics; police statistics